Organizational Culture in Slovenia Foreign Companies (Journal of Universal Excellence, 2026)
Research Question (RQ): Identifying the present organizational culture in foreign companies in Slovenia and orientation types towards individual cultures are reflected in different levels of organization.Purpose: The aim of the research was to investigate prevalent type of organizational culture in selected micro, small, medium and large foreign-owned enterprises in the Republic of Slovenia.Method: Obtaining data and information, questionnaires based on Cameron and Quinn typology were used and sent to 437 different companies.Results: Study participants, employed in Slovenian companies with foreign capital, tend to opt for clan cultures and therefore perceive cultures the market and the hierarchy as company's dominant cultures.Organization:The results obtained from the empirical part of the study contribute to a better understanding of successful foreign companies in Slovenia with such organizational culture.Society: Organizational culture in foreign companies is the basis for the further research of Slovenian economic environment.Originality: Determining, for the very first time, whether there is a higher performance of foreign ownership enterprises, according to the identified type of organizational culture.Limitations/Future Research: There is a great opportunity for further research on identifying the relationship between company's performance and it's stability.
Keywords: companies; management; organizational culture; research; foreign ownership